Women Involved In Drug Dependence In Malaysia An In-Depth Study. - Wong, P.C.; Navaratnam, Profesor Madya (Dr.) V.; Foong, K. (Pusat Penyelidikan Dadah Dan Ubat-Ubatan Universiti Sains Malaysia, 1988)

(untitled)
This study is a follow-up of an epidemiological study published in a report entitled Women Involved 1n Drug Dependence in Malaysia - A Preliminary Study (Foong, Navaratnam and Wong,1987). It was felt that the socio-demographic and drug use patterns data in the preliminary study would not be sufficient to provide a more in-depth understanding of drug dependence among women. This present study 1S conducted to co~t1n~e where the first left off.